The Age-Productivity Profile:Long-Run Evidence from Italian Regions - Federico Barbiellini; Matteo Gomellini; Lorenzon Incoronato; Paolo Piselli (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
This paper leverages spatial and time-series variation in the population age structure of Italian regions to uncover the causal effect of demographic shifts on labour productivity. Such effect is analysed along a 'first-order' channel stemming from the direct relation between an individual's age and productivity, and a 'second-order' channel that captures the productivity implications of a more or less dispersed age distribution. We propose an estimation framework that relates labour productivity to the entire age distribution of the working-age population and employs instrumental variable techniques to address endogeneity issues. The estimates return a hump-shaped age-productivity profile, with a peak between 35 and 40 years, as well as a positive productivity effect associated with a more dispersed age distribution.
Keywords: J11; J21; N30; 330; productivity; demography; age distribution; working-age population; long-run